2022
DOI: 10.1002/cite.202200156
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Flow Sheet Simulation of Selected Mechanical Recycling Processes for Li‐Ion Batteries

Abstract: Dedicated to Prof. Dr.-Ing. Joachim Werther on the occasion of his 80th birthdayTo investigate the mechanical processes of Li-ion battery recycling in more detail, models for the different unit processes are to be developed. Here, model approaches for the cutting mill and the zig-zag-sifter are presented. These models are to be used in dynamic flow sheet simulations, with which the individual unit processes as well as the combination to a small process chain were simulated. Thereby, the dynamic interactions be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As shown by Punt et al [27], electrode foils can be described by the model of Tomas and Gröger [24]. However, in these investigations, untreated electrode foils instead of real recycling products have been investigated, and the separation parameter of the plate-like foils has been particle size instead of settling velocity.…”
Section: Modellingmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown by Punt et al [27], electrode foils can be described by the model of Tomas and Gröger [24]. However, in these investigations, untreated electrode foils instead of real recycling products have been investigated, and the separation parameter of the plate-like foils has been particle size instead of settling velocity.…”
Section: Modellingmentioning
confidence: 99%
“…V H are the volume rates for the light and heavy fraction, the separation velocity v T , the settling velocity v s , and the number of effective separation stages z. This modelling was already used for recycled materials like building scrap [26] and battery materials [27]. Punt et al [27] showed flow-sheet simulations involving a ZZAC to separate the separator foil from electrode foils and anode and cathode foils from each other, implementing the model of Tomas and Gröger.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations